Explaining Adolescent Risk Behaviors Based on Adverse Childhood Experiences and Psychological Status with the Mediating Role of Moral Competencies: A Comparative Model Study in Girls and Boys - Mohebi, Ali; Moradi, Shahab; Sotoudehasl, Nemat; Izadimazidi, Maryam (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study investigated the structural relationships between health-related risk behaviors, adverse childhood experiences, and psychological status by examining the mediating role of protective moral competencies. Methods and Materials: This correlational study was conducted using structural equation modeling. The statistical population included all upper secondary school students in Semnan County during the final quarter of the 2023–2024 academic year. The sample consisted of 1,084 students selected through cluster sampling. Data were collected using the Adolescent Risk-Taking Questionnaire developed by Alizadeh Mohammadi and Ahmadabadi (Alizadeh Mohammadi & Ahmadabadi, 2008), the Moral Competency Questionnaire developed by Martin and Austin (Martin & Austin, 2010), the Childhood Trauma Questionnaire developed by Vanderhart and Vanderlinden (Vanderhart & Vanderlinden, 1999), the NEO Personality Inventory (Costa & McCrae, 1985) (neuroticism dimension only), and the Dark Future Scale developed by Zaleski et al. (Zaleski et al., 2017). Findings: The findings indicated that the indicator variables of risk behaviors and protective moral values loaded significantly and consistently onto these latent constructs (t > 1.96). The effect of protective moral values on risk behaviors was negative and significant. The effects of adverse childhood experiences, unfavorable psychological status, and dark future perception on risk behaviors were positive and significant. In addition, the effects of adverse childhood experiences, unfavorable psychological status, and dark future perception on moral values were negative and significant. The indirect effects of adverse childhood experiences, unfavorable psychological status, and dark future perception on risk behaviors through the mediating role of protective moral values were also significant. Conclusion: The findings emphasized the importance of designing and implementing school-based and family-based interventions focused on strengthening protective moral competencies, promoting mental health, and improving adolescents’ attitudes toward the future. Such approaches may serve as preventive strategies for reducing health-related risk behaviors during adolescence.